THE USE OF VIDEO TO IMPROVE STUDENTS' ACHIEVEMENT IN SPEAKING SKILLS - Adam Mudinillah; Sri Nur Rahmi; Fatimah Zahrah; Ahmad Firdaus Mohd Noor (Lingeduca: Journal of Language and Education Studies, 2026)
Speaking is considered a difficult skill to practice in the teaching and learning process, particularly in Arabic at the Madrasah Aliyah level. This difficulty is caused by several factors. First, some Arabic teachers conduct lessons in a serious atmosphere and prefer to spend classroom time reading books and completing written assignments. They rarely allocate time for students to speak to one another in Arabic. Consequently, students have limited opportunities to practice speaking in the classroom. This study aimed to use video as a learning medium to improve students' achievement in Arabic speaking skills. A quantitative research method was employed, using numerical data-collection techniques. The data were obtained through a questionnaire administered using Google Forms and distributed to respondents who served as the research subjects. The findings showed an improvement in students' ability to speak Arabic through the use of video-based learning media. The study concluded that using video in Arabic learning could improve students' speaking skills and achievement. This study was limited to examining the use of video to improve students' achievement in speaking skills. Future researchers are therefore expected to develop more attractive Arabic-language video learning media and to make their use a productive challenge in the Arabic learning process.